Effect of Vermicompost on Growth of Coconut Seedlings under Field Conditions in Sri Lanka - Senarathne, S. H. S. (International Coconut Community, 2018)
Organic matter contributes in maintaining soil fertility in agriculture. Vermicompost is rich in plant nutrients and recognized as potential organic manure source for many crops. In this experiment, different amount of vermicompost and inorganic fertilizers were tested. The objective of the research was to evaluate the effect of vermicompost on the growth of coconut seedling in the field conditions and to reduce the cost of production of coconut plantations. Treatments were arranged in a Randomized Complete Block Design (RCBD) with three replicates. The experiment consisted of three different fertilizer treatments with vermicompost (100%) + Dolomite 500g (T1), Inorganic fertilizer (Young Palm Mixture) + Dolomite (T2) and vermicompost + Inorganic fertilizer (Young Palm Mixture) + Dolomite (T3). Growth measurements revealed A significantly higher seedling girth, leaf production rate and early highest coconut seedling flowering percentage in the vermicompost base integrated fertilizer applied treatment when compare with other two treatments. This experiment had brought out that application of vermicompost base integrated fertilizer application system is beneficial for coconut seedlings in the field for the better field establishment and vigorous seedling growth.